2022
DOI: 10.3390/w14121930
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Depuration Plants on Nutrient Levels in the North Adriatic Sea

Abstract: Macronutrients (nitrogen—N; phosphorus—P; silicon—Si) play a crucial role in ocean surface waters stimulating the planktonic primary production; in fact, their concentrations are fundamental for the evaluation of the trophic status of the water body and eutrophication phenomena. Loads of nutrients into the sea are mainly represented by river runoff and depuration plant outflows. For this purpose, in the framework of the AdSWiM project, “Managed use of treated urban wastewater for the quality of the Adriatic Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…PTE concentration did not significantly differ between wastewater and seawater samples, although other parameters (e.g., nutrient concentration and microbial indicators) need to be investigated to identify possible synergistic effects. Some differences were observed in the composition of the WWTP effluents between Italian and Croatian plants because of the different source of waters converging to the depuration plants [41][42][43].…”
Section: Wp 42: Characterization Of Treated Ww and Of The Seawater In...mentioning
confidence: 99%
See 1 more Smart Citation
“…PTE concentration did not significantly differ between wastewater and seawater samples, although other parameters (e.g., nutrient concentration and microbial indicators) need to be investigated to identify possible synergistic effects. Some differences were observed in the composition of the WWTP effluents between Italian and Croatian plants because of the different source of waters converging to the depuration plants [41][42][43].…”
Section: Wp 42: Characterization Of Treated Ww and Of The Seawater In...mentioning
confidence: 99%
“…In this study, a plastic electrode based on graphite, a PVC binder [49,50], and an in-house synthesized organic derivative of molybdate anion (MOP) [51] was prepared as the first approach to develop an electrochemical DIP sensor (Figure 4A). Prior to electrode preparation, surface waters of the northern Adriatic Sea were characterized, and nutrient concentrations were measured during a whole season using classical analytical techniques [41,42]. After determination of the baseline nutrient content, the electrode was prepared and optimized for its use as a phosphate sensor.…”
Section: Wp 43: An Electrochemical Sensor (E-sensor) For Phosphate De...mentioning
confidence: 99%
“…In particular, the Adriatic Sea is considered further vulnerable to contamination due to its semi-enclosed morphological structure, low bathymetry, and high river inputs. Moreover, several studies have reported that the sea zones close to the wastewater outfall pipelines are particularly sensitive and vulnerable to pollution such as high concentrations of nutrients, fecal indicator bacteria (FIB), and pharmaceutically active compounds [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%